Translation Quality of Level Shift for English Noun Phrase into Indonesian. - Haryanti, Dwi (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
The aim of this article is describing the translation quality of English noun phrasestranslated into Indonesian. The data of this descriptive qualitative study are phrases,clauses, and sentences containing of noun phrases found in English scientific and fictiontexts translated into Indonesian. The data were analyzed by applying translation theoriesproposed by Nababan (2012) and Lauscher (2000). Based on the analyzed data, there arethree elements of translation quality show accurate, acceptable, and readable. Allvariation of English noun phrase patterns translated into Indonsian have same meaningto the message of the source language. They are acceptable and easy to understand withoutreading the entire translation more than one. Therefore, the translation of noun phrasesare readable for ideal readers of the translated texts. The result of this study can beapplied in teaching learning process of translation subject, theory, practice, and evaluationin translation.